The role of urban planning and design in responding to climate change: the Brisbane experience - Kozlowski, Marek; Mohd Yusof, Yusnani (Emerald Group Publishing, 2016)
Purpose: The purpose of this paper is to discuss the responses from the urban planning and design professions in Brisbane to the impacts of climate change and the implications of the 2011 flood. In the past decade, the ramifications of climate change have already left a scar on some of the urban regions round the world. The Australian continent has been regarded as one of the most affected regions in terms of climate change implications. The 2011 Queensland floods of historic proportion, which came after a decade of extreme drought, raised many questions about the future development of cities. For the past decades, Queensland’s economy was largely based on property-led development. The flood plain land situated along Brisbane River has been developed and overburdened with building infrastructure contributing to the magnification of the flood events. Design/methodology/approach: The research methodology is based on identification of the problem and the major objective. To address the objective, this study concentrated mainly on the use of qualitative research methods. The major qualitative research methods include literature review, qualitative analysis and observations. Brisbane, the capital of the Australian state of Queensland, has been selected as the case study area. Findings: The paper revealed strong regional and city-wide planning directives addressing climate change which has not yet been fully been translated at the local-neighbourhood level. Originality/value: This paper provides a deep insight analysis and evaluation of the design and planning measures currently used to combat the impacts of climate change.